The critical incident technique in physiotherapy education - Johlyne C. Beenhakker (AOSIS, 1980)
Report of a pilot study undertaken to determine the behaviour of an effective physiotherapist. The critical incident technique was used to collect data from 30 practising physiotherapists and 300 separate incidents of effective and ineffective behaviour were identified. On the basis of this study, the desirability of objectively identifying curriculum content in physiotherapy education has been established.